Climate change, environmental NGOs and public awareness in the Netherlands: Perceptions and reality - Banu Bayramoéglu Lise; Wietze Lise (Fondazione Eni Enrico Mattei (FEEM), 2002)
The climate change issue has been widely studied. To add to this literature, this paper focuses on the role of environmental non-governmental organizations in the Netherlands in raising public awareness. Besides, their role in relation to the Dutch government's climate policies is researched as well. The findings of this research indicate that, with respect to the climate change issue, environmental NGOs in the Netherlands may not always be active and systematic, as it is generally perceived, in raising public awareness and putting pressure on the Dutch government for implementing the targeted measures at the national level.
Keywords: 330